NARRATIVE PECULIARITIES OF EPISTOLARY DIALOGUE «OLHA KOBYLIANSKA – LESIA UKRAINKA»: FROM THE BIOGRAPHICAL AUTHOR TO THE NARRATOR - Ільків, А. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article deals with narrative peculiarities of the intimate letter in the context of modernist aesthetics. The aim of the articleis to research the narrative models of the intimate letters of Olha Kobylianska and Lesia Ukrainka and to trace the origin of intimate metalanguage of these letters, decoding key symbols. The article examines the narrative peculiarities of indirect epistolary dialogue of the best representatives of Ukrainian modern literature. The problem of distinction of the biographical author, the author in the texts of a letter and the narrator of the epistolary text is analyzed. It is discovered that the epistolary dialogue of Lesia Ukrainka with Olha Kobylianska has become a new verbal space of releasing woman’s energy sublimated into special woman’s narration that is new for the Ukrainian literature, a space for deep self-analysis of the epistolary communicators, articulation and transmission of their own biographical experience. Epistolary metalanguage, created by the writers, is examined in the context of narration as well as psychoanalysis as the indicator of a peculiar soul intimacy of the communicators in order to pressurize, even sacralize a texthrough taboo on names.